Zoning Study on the Influence of Sluice Operation on Flood Drainage of Plain River Network. Issue 1 (1st April 2022) - Fang, Zhihao; Li, Dongfeng; Wang, Yanfei; Hu, Donghui; Li, Zihao
Abstract: The drainage of river network in Yaobei plain is of great significance to the social and economic development of Yuyao and Ningbo. Linhai Pujiang gate and Taojia Road gate are two important gates for drainage of the river network in Yaobei plain. With the different time of opening the gate for dispatching, the water level reduction values of different towns, streets and communities in the river network are different. If the water level decline in the river network area is classified according to a certain way, the impact degree and impact range of sluice drainage on river network drainage can be studied, so as to classify and partition the impact of drainage according to the degree of impact, township streets can formulate different drainage countermeasures. Therefore, it is of great significance to study the impact of gate operation on river network drainage. In order to fully study the flood drainage function of the sea gate of Yaobei plain river network, based on the preliminary establishment and verification of the plane two-dimensional mathematical model of Yuyao plain river network, this paper calculates the changes of water level and velocity in different areas of towns and streets of Yuyao river network with time and region after the flood drainage operation of the gate for 7 hours under different conditions, according to the range of water level drop of 0.05m and different numerical ranges, this paper classifies the influence areas of large gate drainage on Yaobei river network drainage, and obtains seven partitions of the influence of large gate dispatching on Yaobei river network drainage. According to this partition, the regional river network drainage countermeasures are preliminarily analyzed, which provides a reference basis for the drainage decision-making of township streets.